2013
DOI: 10.5005/jp-journals-10024-1450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lycopene in the Treatment of Periodontal Disease: A Clinical Study

Abstract: Purpose: Several epidemiologic studies have suggested a role of tomato products in decreasing the risk of the development of diseases related to oxidative stress (cancer and other chronic diseases). Oxidative stress may result in periodontal tissue damage either directly or indirectly. Lycopene, a powerful antioxidant and the main carotenoid in tomato products possesses the greatest quenching ability of singlet oxygen among the various carotenoids and is effective in protecting blood lymphocytes from NOO-radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 15 publications
0
33
0
1
Order By: Relevance
“…A study by Chandra et al suggested that lycopene supplementation may enhance the improvement of periodontal health [ 104 ]. Similarly, later studies have also found a possible therapeutic role of lycopene in the management of periodontitis [ 105 , 106 ]. To date, the exact mechanism of action of lycopene in the periodontium has not been established.…”
Section: Antioxidants and Periodontal Healthmentioning
confidence: 95%
“…A study by Chandra et al suggested that lycopene supplementation may enhance the improvement of periodontal health [ 104 ]. Similarly, later studies have also found a possible therapeutic role of lycopene in the management of periodontitis [ 105 , 106 ]. To date, the exact mechanism of action of lycopene in the periodontium has not been established.…”
Section: Antioxidants and Periodontal Healthmentioning
confidence: 95%
“…Although carotenoids are known as playing an important role in the prevention of inflammatory diseases, the clinical efficacy for periodontitis may be only beginning to be investigated now (Table 1). Periodontitis patients, N = 20 Improvement of periodontal healing [43] Periodontitis patients, N = 100…”
Section: Carotenoids and Periodontitismentioning
confidence: 99%
“…Arora et al, reported that systemic lycopene administration suppressed salivary IL-1 levels, resulting in inhibition of periodontal inflammation [42]. Belludi et al, have also reported that lycopene is an effective carotenoid in patients with periodontitis clinically [43]. Although number of subjects in the clinical study was very limited, significant improvement of periodontal healing was observed after oral prophylaxis in Lycopene-treated group compared with control group.…”
Section: Lycopenementioning
confidence: 99%
“…Systemic supplementation of 8 mg/day of lycopene was reported to decrease the gingival index in patients with gingivitis [88]. In individuals with chronic periodontitis, it was reported that the supplementation of 4 mg/day of oral lycopene in addition to SRP for 2 weeks resulted in a reduction in clinical attachment loss [89]. Arora et al [90] found that, in individuals with CP, 8 mg/day of oral lycopene intake for 2 months in addition to SRP had positive effects in plaque index, modified gingival index, probing bleeding, and saliva IL-1β compared to the control group but reported that there was no significant difference in terms of a reduction in pocket depth, clinical attachment, and serum TNF-α levels.…”
Section: Carotenoidsmentioning
confidence: 99%